RISK PERCEPTION OF CONSUMERS' WILLINGNESS TO BUY SHARIA INSURANCE PRODUCTS AS A FORM OF SHARING OF RISK ACTION - Sekarwati Saputro (IAIN Surakarta, 2022)
This study aims to analyze the influence of risk perception on consumers' willingness to buy Sharia insurance in Wonogiri Regency. This research is included in quantitative research. The population of this study is a resident of Wonogiri district who is Muslim. The sample collected in this study was as many as 100 respondents. Sample selection technique is to use purposive sampling where the sample is determined based on certain criteria. SmartPLS 3.0 is used in research as an analytical tool. The results of this study show that (1) The chance of disaster has no effect on the willingness to buy Sharia insurance. (2) The chance of disaster has a significant positive effect on the fear of the individual. (3) Individual fear has a significant positive effect on the willingness to buy Sharia insurance. (4) Individual fears mediate between the chance of disaster and the willingness to buy Sharia insurance. (5) Experience has a significant positive effect on the willingness to buy Sharia insurance. (6) Experience has no effect on individual fears. (7) The fear of individuals is not able to mediate between experience and willingness to buy Sharia insurance.